2008
DOI: 10.1098/rspb.2008.0715
|View full text |Cite
|
Sign up to set email alerts
|

Dinosaurs and the Cretaceous Terrestrial Revolution

Abstract: The observed diversity of dinosaurs reached its highest peak during the mid-and Late Cretaceous, the 50 Myr that preceded their extinction, and yet this explosion of dinosaur diversity may be explained largely by sampling bias. It has long been debated whether dinosaurs were part of the Cretaceous Terrestrial Revolution (KTR), from 125-80 Myr ago, when flowering plants, herbivorous and social insects, squamates, birds and mammals all underwent a rapid expansion. Although an apparent explosion of dinosaur diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
319
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(341 citation statements)
references
References 66 publications
18
319
3
1
Order By: Relevance
“…; and (2) are significant diversification shifts concentrated in any specific interval of time? By comparing their cladogram to one expected under the null "birthdeath" model, Lloyd et al (2008) identified several nodes that exhibit significant diversification shifts. These are essentially nodes that are significantly more speciose than their sister taxon, which is a violation of the null model that assumes random splitting over time (see Moore, 2002, 2005;Jones et al, 2005).…”
Section: Taxonomic Diversity and Significant Diversification Shiftsmentioning
confidence: 99%
See 2 more Smart Citations
“…; and (2) are significant diversification shifts concentrated in any specific interval of time? By comparing their cladogram to one expected under the null "birthdeath" model, Lloyd et al (2008) identified several nodes that exhibit significant diversification shifts. These are essentially nodes that are significantly more speciose than their sister taxon, which is a violation of the null model that assumes random splitting over time (see Moore, 2002, 2005;Jones et al, 2005).…”
Section: Taxonomic Diversity and Significant Diversification Shiftsmentioning
confidence: 99%
“…Diversity measurements continually change as new fossils are discovered and specimens are reinterpreted (for instance, compare the dinosaur diversity measurements of Dodson (1990) and Wang and Dodson (2006)). A profile of dinosaur diversity over time was recently provided by Lloyd et al (2008), who were also the first authors to provide a phylogenetic correction to diversity measures across all Dinosauria (based on a supertree of dinosaur phylogeny, which as a "summary tree" is a broad and inexact proxy for a correction) and examine the potential sampling biases implicit in the dinosaur fossil record. Their diversity curves, based both on observed fossils ("taxic estimate") and observed counts corrected for ghost lineages ("phylogenetic estimate"), indicate a steady increase in diversity from the Carnian through the Early Jurassic (Table 4).…”
Section: Taxonomic Diversity and Significant Diversification Shiftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite 30 years of intensive research, a fundamental question remains: were dinosaurs undergoing a long-term decline before intensive volcanism and the Chicxulub bolide impact in the latest Cretaceous, or did these contingencies of Earth history strike down dinosaurs during or near their prime (at a time when their global biodiversity was stable or even increasing) [3][4][5][6][7][8][9][10][11][12][13][14][15] ?…”
mentioning
confidence: 99%
“…Diversity counts, however, are problematic because of the emerging realizations that observed taxonomic richness is heavily biased by uneven sampling of the fossil record 16,17 and that many supposed Late Cretaceous dinosaur species are likely juveniles or sexual morphs of other known taxa [18][19][20] . Attempts to 'correct' terminal Cretaceous diversity counts for such biases have produced conflicting results [10][11][12][13][14][15] . Similarly, abundance measures are also potentially distorted by taphonomic and palaeoenvironmental heterogeneity over time 21 .…”
mentioning
confidence: 99%